The effectiveness game-based learning approach in improving problem-solving skills and learning motivation - Nur Anisa Dika Maharani; Andriyani (Journal of diversity in learning (JDIL), 2022)
This study aimed to determine the effectiveness of the problem-based learning model with a game-based learning approach in improving problem-solving skills and motivation to learn statistics at SMKN 5 Yogyakarta. The type of research used is classroom action research, carried out in two cycles, and each cycle goes through the stages of planning, implementation, observation, and reflection. Data collection techniques in this study used problem-solving skills tests, activity observations, and questionnaires to measure students' learning motivation. The sample of this research was 22 students of class X-A, Department of Batik and Textile Creative Craft, carried out for one month. The results showed an increase in the average problem-solving skills of students in the initial conditions, Cycles I and II, respectively, namely 13.43; 64.95; and 78.35. Meanwhile, the average score of students' learning motivation has increased from the initial conditions, Cycles I to II, respectively, namely 82.86 (medium category); 91.05 (high category); and 104.95 (very high category). From the results of this study, it can be concluded that the problem-based learning model with a game-based learning approach effectively improves problem-solving skills and student motivation in statistics material.